Audit of the Handover in Resident Doctors’ First On-call Rota - Ayah Ibrahim (BJPsych Open)
Aims: Handover is ‘the accurate reliable communication of task-relevant information across shift changes or between teams thereby ensuring continuity of safe and effective working’. Handover is of critical importance; this ensures high quality care of our patients. Therefore this audit Aims: